2016
DOI: 10.1089/jwh.2015.5438
|View full text |Cite
|
Sign up to set email alerts
|

Can Postpartum Depression Be Managed in Pediatric Primary Care?

Abstract: Postpartum depression can be managed within PPC. Psychosocial strategies can be integrated as part of anticipatory guidance. Critical supports for primary care clinicians, especially in pediatric practices, are needed to improve access to timely nonstigmatizing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 69 publications
1
26
0
3
Order By: Relevance
“…Successful referral and treatment is possible in primary care settings. 39 These reasons support the strong level of screening occurring in pediatric practice.…”
Section: Discussionmentioning
confidence: 89%
“…Successful referral and treatment is possible in primary care settings. 39 These reasons support the strong level of screening occurring in pediatric practice.…”
Section: Discussionmentioning
confidence: 89%
“…Even brief psychosocial interventions within primary care settings have shown to be efficacious. 129 Recent studies have revealed that supports to increase maternal engagement and responsiveness can reverse gene expression patterns related to stress via epigenetic pathways and, thereby, buffer initial adverse effects of perinatal depression (DNA methylation and neuroendocrine functioning). 130…”
Section: Effect On the Childmentioning
confidence: 99%
“…A total score of 10 or more on the EPDS is a positive screen indicating a concern for depression, which necessitates further discussion in which providers can clarify the findings, determine acuity of concerns, and, if necessary, make appropriate referrals for further assessment and treatment of the parent (as described below). 129,163 It is important to note that similar to all screening tools, the EPDS is not a diagnostic instrument. In situations in which there is any indication of suicidal ideation (on the EPDS question 10 or in discussion), if the parent expresses concern about his or her ability to maintain the infant's safety, or if the pediatric provider suspects that the parent is suicidal or homicidal, it is considered a positive screen that warrants an immediate evaluation for safety of the parent and/or infant, often in an emergency psychiatric setting.…”
Section: Perinatal Depression Screening Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have not explored a pediatric role in depression screening and referral from the fathers' perspective, there is evidence that maternal postpartum depression can be adequately managed within pediatric primary care. 5 Nevertheless, overall screening rates are low, and 80% of pediatric residents report not receiving any training to manage adult mental health problems. 6 This finding underscores opportunities to educate physicians about the importance of depression in both parents and to develop strategies to integrate screening tools into routine care.…”
Section: Prevalence Of Depression Among Fathers At the Pediatric Wellmentioning
confidence: 99%